2014
DOI: 10.5603/piap.2014.0014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic Obstructive Pulmonary Disease (COPD) on Patient’s Life and His Family

Abstract: Introduction: Chronic Obstructive Pulmonary Disease (COPD) is one of the most common chronic diseases of adults and is a major cause of chronic morbidity and mortality throughout the world. It is the cause of physical and mental suffering for the patient, significantly impairs quality of life, reduces the vital activity and affects the patient’s life in its various aspects. In 2012, the nationwide survey was conducted in COPD outpatients with a history of smoking exploring the various factors of the disease an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
(15 reference statements)
1
17
0
1
Order By: Relevance
“…For example, 16% of couples declared that smoking had a negative impact on their relationship and 42% stated that smoking had a negative impact on the family budget [30]. Furthermore, for some caregivers the coughing caused feelings of disgust, leading to difficulties in kissing their loved one [26].…”
Section: Impact On Informal Caregiversmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, 16% of couples declared that smoking had a negative impact on their relationship and 42% stated that smoking had a negative impact on the family budget [30]. Furthermore, for some caregivers the coughing caused feelings of disgust, leading to difficulties in kissing their loved one [26].…”
Section: Impact On Informal Caregiversmentioning
confidence: 99%
“…Furthermore, for some caregivers the coughing caused feelings of disgust, leading to difficulties in kissing their loved one [26]. This, together with the fact that sexual intercourse was considered too strenuous for the patient, changed the intimate relationship [26,30,35]. Although almost all caregivers felt that the patient needed their support [26], some caregivers persevered because of a sense of duty described in terms of marriage vows and societal expectations [31].…”
Section: Impact On Informal Caregiversmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found that according to GOLD 2007 classification, among the 2597 COPD patients under the care of a primary care physician, more than half of the subjects (56.7%) presented severe COPD. Those proportions differ from some observed in outpatient specialist care and GP's, where 47-55% of patients had moderate COPD severity stage [7][8][9]. In cross-sectional studies, the proportion of patients presenting a particular severity stage of the disease depended on the study population as well as the study protocol.…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, in the COPD cohort 57% of patients admitted current smoking and 43% declared smoking in the past. The negative impact of smoking on family relations was declared by 16.4% of respondents [16].…”
Section: Why Do the Polish Citizens Need The Programme?mentioning
confidence: 99%